Dyssol—An open-source flowsheet simulation framework for particulate materials - Vasyl Skorych; Maksym Dosta; Stefan Heinrich (SoftwareX, 2020)
Dyssol is a modelling framework for the dynamic flowsheet simulation of processes designed for handling of particulate materials. Main distinctive features of this software are the comprehensive description of multidimensionally distributed particulate materials, the application of transformation matrices and the use of sequential-modular simulation approach. This cross-platform system can be easily extended with new models, applied for calculation of large datasets and coupled to the external programme packages.